'What matters to you?' Health outcome prioritisation in treatment decision-making for older patients. (3rd August 2021) - Festen, Suzanne; van Twisk, Yvette Z; van Munster, Barbara C; de Graeff, Pauline
Abstract: Background: for shared decision-making, it is important to discuss of the patients' priorities in order to align treatment decisions with these priorities. Objective: to assess the most important health outcome for older patients on the verge of making a treatment decision, using the Outcome Prioritization Tool (OPT). Secondary objectives were the feasibility of the OPT and patient variables associated with prioritising different health outcomes. Design: retrospective cohort study. Setting and subjects: at the University Medical Hospital Groningen, the Netherlands, 350 patients were included who visited the geriatric outpatient clinic during the work-up regarding a complex treatment decision (such as cancer treatment or heart valve replacement). Methods: during geriatric assessment, patients prioritised between four health outcomes, using the OPT. Results: median age was 78.5 years, 172 (49.1%) were referred regarding a treatment decision for a malignant disease. Cognitive impairment was present in 23.6%. Most patients (55.2%) prioritised maintaining independence as their most important goal, followed by extending life in 21.1%. Only cognitive impairment was significantly associated with prioritising extending life as the most important health outcome. For 107 patients (30.6%), the OPT was not feasible; these patients more often had malnutrition and assisted living. Conclusions: the main health outcome of older patients on the verge of making a treatment decision was maintaining independence, followed by extending life. Patients with cognitive impairment more often prioritised extending life. The OPT was feasible as a decision aid for most patients. For optimal shared decision-making, it is crucial to take patient preferences into account.